Mengkaji Relevansi Etika Pemasaran Bank Syariah Di Era Marketing Digital - Andry Rani Putri Praduita Asmara; Romi Adetio; Yenti Sumarni (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2025)
This research examines the relevance of Islamic banks' marketing ethics in the era of digital marketing, which is characterized by global connectivity, rapid information access, interactivity, and personalization. The development of digital technology has brought fundamental changes in the way banks interact with customers, with the adoption of social media, e-commerce, big data, and artificial intelligence for more interactive and personalized marketing. While offering efficiency and wide market reach, the digital era also presents ethical challenges, including issues of data privacy, information transparency, and potential manipulation of consumer behavior. This study analyzes how sharia marketing ethics, with its basic principles such as honesty (shiddiq), trustworthiness (amanah), justice (adl), and sharia compliance (ittiba' al-shariah), remains highly relevant and even crucial to maintain trust amidst the torrent of digital information that is often manipulative. The theoretical study includes the relevance of ethics in general, conventional marketing ethics, sharia marketing ethics in depth, as well as the concept of marketing digitalization and its weaknesses and advantages. The results show that sharia marketing in the digital era has high relevance because it is able to answer the challenges of the times without sacrificing the principles of sharia. Islamic ethical values become a strong foundation in dealing with potential ethical deviations in the digital space, such as misleading advertisements, data exploitation, and promos.